A Comprehensive Method for Assessing Marine Resource Governance: Case Study in Kāne'ohe Bay, Hawai'i. Issue 4 (3rd July 2016) - Battista, Willow; Kelly, Ryan P.; Erickson, Ashley; Fujita, Rod
ABSTRACT: A recent metaanalysis identified certain management attributes that are associated with successful management of threshold-based systems. However, high variance among case studies indicates that these attributes do not guarantee good conservation outcomes, suggesting that additional factors may be at play. To better understand these additional factors, we compiled a list of effective governance attributes from the literature, and developed guidance for systematically evaluating their presence, absence, and the extent to which each attribute is actually manifested in a given case study. We also examine the distribution of rights and responsibilities within a system, and the resulting impacts on stewardship incentives. Here we present the results of this analysis as applied to Kāneohe Bay, Hawai'i. Our results confirm that absent or incomplete effective governance attributes can negatively impact conservation outcomes. In Kāneohe Bay, a public-private partnership temporarily compensated for gaps and weaknesses in the governance system, thereby creating conditions conducive to successfully reducing populations of invasive algae. However, this partnership has since dissolved and current capacity to address this and other issues in this system is again lacking. Failure to fix governance weaknesses may compromise the continued health and functioning of the Kāne'ohe Bay system.